Ethnobotany of Wild and Semi-wild Edible Plants of Konso Ethnic Community, South Ethiopia - Addis, Getachew; Asfaw, Zemede; Woldu, Zerihun (Ethnobotany Research and Applications, 2013)
This paper presents the knowledge on wild/semi-wild edible plant species (WEPS) of Konso ethnic community of southern Ethiopia. Ethnobotanical information was collected through focus group discussions, observations, interviews, and preference ranking. A total of 154 edible parts were recorded from 127 plant species with fruit (71), leaves (35) and tubers/roots (18) accounted for the major edible parts. Fruit of Opuntia ficus-indica L., and leaves and young shoots of Leptadenia hastata Vatke were most sought after. Excessive harvesting and acquisition of land for crop cultivation is currently threatening Canthium pseudosetiflorum Bridson, Hyphaene thebaica (L.) Mart., Ficus sycomorus L. and O. ficus-indica, among others. Wise use of these plant species would ensure their sustainable availability and local food sovereignty.